(untitled) (Research, Society and Development, 2022)
The study aimed to evaluate the relationship between pharmaceutical care aimed at dyslipidemic patients who used medications for the treatment of dyslipidemia and the impact on clinical and humanistic outcomes. This was a randomized clinical study with dyslipidemic patients treated at a medication dispensing pharmacy of the Strategic Component of Pharmaceutical Assistance, by meeting the inclusion criteria of the Clinical Protocol and Therapeutic Guidelines - Dyslipidemia: prevention of cardiovascular events and pancreatitis, with the medications standardized: atorvastatin, pravastatin, bezafibrate, ciprofibrate and fenofibrate. After the implementation of pharmaceutical care, patients had reduced blood pressure levels and LDL cholesterol and triglycerides, as well as increased HDL cholesterol levels and reduced cardiovascular risk. Pharmaceutical care was also able to reduce the number of hospitalizations. Additionally, after the pharmacotherapeutic follow-up, there was a change in the assisted’s perception of quality of life, in terms of the environment, as well as an improvement in the level of user satisfaction in relation to the management of therapy/pharmaceutical service domain. Pharmaceutical interventions reduced the occurrence of problems related to pharmacotherapy regarding pharmacotherapeutic effectiveness. In conclusion, the positive impact of clinical and humanistic outcomes was demonstrated, highlighting the importance of pharmacotherapeutic follow-up in dyslipidemia and the fundamental role of the pharmacist in guiding the patient in relation to eating habits, preventing the worsening of the disease, reducing serum levels of lipids and other risk factors, which can reduce the chances of cardiovascular diseases and contribute to the improvement of pharmaceutical care, generating greater satisfaction and, mainly, quality of life for the patient.